Efektivitas Instrumen Tes Uraian Dibandingkan dengan Tes Pilihan Ganda dalam Mengukur Hasil Belajar Siswa di MAN 2 Bantul - Muhammad Syauqi Firdaus; Wahyu Kholis Prihantoro; Latifaturrohmah Latifaturrohmah; Husna Rifaatul Mahmudah; Afrida Aunil Illah (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Learning assessment is a crucial element in the educational process that aims to measure how well students understand the material taught. The tools chosen for measurement have a significant influence on the validity and accuracy of the assessment results. At MAN 2 Bantul, educators generally use two types of measurement tools, namely multiple-choice tests and essay tests. This study aims to assess the effectiveness of essay tests in comparison with multiple-choice tests in assessing student learning achievement at MAN 2 Bantul, using the direct interview method. This study was conducted to gain insight into the views of teachers and students regarding the effectiveness of both types of tests in the educational evaluation process. Data were collected through direct interviews with teachers and students who had experience in using both types of measurement tools. Data analysis was obtained using a descriptive qualitative approach to explore their views and experiences regarding the accuracy and appropriateness of tests in assessing learning outcomes. The findings from the interviews showed that multiple-choice tests were considered more effective and practical in measuring student learning outcomes because they used the JMD (Jogja Madrasah Digital) application, which immediately displayed the scores. However, the teachers also agreed that essay tests provided a more comprehensive analysis of learning outcomes because they encouraged students to think critically. This study recommends the implementation of a combination of both types of exams to make learning evaluation more efficient.